Weathering and trace element mobilisation of MSWI bottom ash from wet and dry extraction - Ingold, Philipp; Weibel, Gisela; Kämpfer, Patrick; Churakov, Sergey V. (Journal of contaminant hydrology, 2025)
This study aims on the characteristics of occurring weathering processes of dry and wet extracted bottom ash materials and its effects on element emissions. To examine the role of initial water contact, dry bottom ash was experimentally moistened. Titration experiments were performed to elaborate buffer capacities and dissolution processes of the waste residues as a function of pH, and thermodynamic calculations were used to identify the solubility-controlling phases. Dry bottom ash showed highly alkaline in-situ pH conditions (pH 12.6). Continuous acid addition revealed a multi-stage process, which was characterised by the formation and dissolution of different phases across four different buffer systems, including portlandite dissolution and formation of ettringite and CSH phases in the first stage (pH > 12.1), dissolution of ettringite and CSH phases in the second stage (pH 9.7–12.1), carbonate dissolution during the third stage (pH 5.5–9.7), and dissolution of Al- and Fe-hydroxides in the fourth stage (pH < 5.5). Prior weathering processes in the moistened dry bottom ash and wet bottom ash resulted in a reduction of the in-situ pH (pH 12.1 and 10.3, respectively). Thermodynamic calculations suggested that phases containing Ca, S, Al, and Si were mainly responsible for the pH stabilisation. Emission trends as a function of pH generally aligned with calculated solubility curves, with dry bottom ash showing higher concentrations than wet bottom ash. Discrepancies, especially found in the dry bottom ash system, may be associated with elevated the presence of ligands (i.e., DIC, DOC), enhancing the mobility of selected elements (Al, Cu, Zn). Bottom ashes investigated in this study are subject to environmental contaminants and potential hazards. Their characterisation and behaviour investigated during this work provides further insight into their behaviour and highlights the enhanced leaching of dry extracted bottom ash under naturally and environmentally relevant conditions. •Weathering of wet and dry bottom ash by acidification is a multi-stage process.•Dry bottom ash shows enhanced element emissions compared to its wet counterpart.•Thermodynamic calculations suggest solubility-controlled element mobilisation.•Increased presence of ligands enhances mobilisation of selected trace elements.•Landfilling of dry bottom ash increases landfill leachate pH and element emissions.